Identification of a Phosphorylation-Dependent Nuclear Localization Motif in Interferon Regulatory Factor 2 Binding Protein 2 - Teng, Allen C. T.; Al-montashiri, Naif A. M.; Cheng, Brian L. M.; Lou, Philip; Ozmizrak, Pinar; Chen, Hsiao-Huei; Stewart, Alexandre F. R. (Université d'Ottawa | University of Ottawa, 2011)
Background - Interferon regulatory factor 2 binding protein 2 (IRF2BP2) is a muscle-enriched transcription factor required to activate vascular endothelial growth factor-A (VEGFA) expression in muscle. IRF2BP2 is found in the nucleus of cardiac and skeletal muscle cells. During the process of skeletal muscle differentiation, some IRF2BP2 becomes relocated to the cytoplasm, although the functional significance of this relocation and the mechanisms that control nucleocytoplasmic localization of IRF2BP2 are not yet known. // Methodology/Principal Findings - Here, by fusing IRF2BP2 to green fluorescent protein and testing a series of deletion and site-directed mutagenesis constructs, we mapped the nuclear localization signal (NLS) to an evolutionarily conserved sequence 354ARKRKPSP361 in IRF2BP2. This sequence corresponds to a classical nuclear localization motif bearing positively charged arginine and lysine residues. Substitution of arginine and lysine with negatively charged aspartic acid residues blocked nuclear localization. However, these residues were not sufficient because nuclear targeting of IRF2BP2 also required phosphorylation of serine 360 (S360). Many large-scale phosphopeptide proteomic studies had reported previously that serine 360 of IRF2BP2 is phosphorylated in numerous human cell types. Alanine substitution at this site abolished IRF2BP2 nuclear localization in C2C12 myoblasts and CV1 cells. In contrast, substituting serine 360 with aspartic acid forced nuclear retention and prevented cytoplasmic redistribution in differentiated C2C12 muscle cells. As for the effects of these mutations on VEGFA promoter activity, the S360A mutation interfered with VEGFA activation, as expected. Surprisingly, the S360D mutation also interfered with VEGFA activation, suggesting that this mutation, while enforcing nuclear entry, may disrupt an essential activation function of IRF2BP2. // Conclusions/Significance - Nuclear localization of IRF2BP2 depends on phosphorylation near a conserved NLS. Changes in phosphorylation status likely control nucleocytoplasmic localization of IRF2BP2 during muscle differentiation.